1990
DOI: 10.1161/01.hyp.15.5.519
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hyperinsulinemia and blood pressure. Interaction with catecholamines?

Abstract: Although hyperinsulinemia and increased adrenergic activity have been postulated to be important factors in obesity-associated hypertension, a cause and effect relation between insulin, catecholamines, and hypertension has not been established. The aim of this study was to determine whether chronic hyperinsulinemia, comparable with that found in obese hypertensive patients, causes hypertension in normal dogs, increases plasma catecholamines, or potentiates the blood pressure effects of norepinephrine. In six n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 29 publications
4
42
0
Order By: Relevance
“…Therefore, an insulin-induced structural change in resistance vessels may be responsible for increased peripheral resistance or lead to increased sensitivity to vasoconstrictor agonists. However, neither chronic hyperinsulinaemia associated with insulinoma in man [51] nor prolonged intravenous administration of insulin to dogs for up to 28 days [52] have been shown to elevate blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an insulin-induced structural change in resistance vessels may be responsible for increased peripheral resistance or lead to increased sensitivity to vasoconstrictor agonists. However, neither chronic hyperinsulinaemia associated with insulinoma in man [51] nor prolonged intravenous administration of insulin to dogs for up to 28 days [52] have been shown to elevate blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…2. Insulin resistance was also suggested to participate in the pathogenetic mechanisms of hypertension (Rahmouni et al 2003), but there is considerable evidence against its major role in obesity (Hall et al 1990, Rocchini et al 2004.…”
Section: The Role Of Snsmentioning
confidence: 99%
“…Insulin has vasodilative and hypotensive effects (3)(4)(5)(6)(7)(8)(9). It has been reported that hypertension was improved by insulin treatment in patients with DM (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that hypertension was improved by insulin treatment in patients with DM (10)(11)(12). The antihypertensive effect of insulin was explained either by the secondary action of improved glucose metabolism after insulin treatment or by the direct action on peripheral arterial vessels (4,(10)(11)(12)(13)(14)(15)(16). Peripheral arterial resistance is a critical factor for the regulation of diastolic blood pressure, which is increased by atherosclerosis or vasoconstriction (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%